ANALISIS PENGARUH MODAL DAN TEKNOLOGI TERHADAP PRODUKSI INDUSTRI IKAN DI SIBOLGA - PERTAMA YUL ASMARA PANE (LP2MTBM MAKARIOZ, 2021)
The marine and fisheries sector is one of the economic sectors that have a role in national economic development,especially in the provision of protein food, foreign exchange acquisition and employment provision. Capital is the cost used toproduce or buy goods to be sold and the costs used to help run their business. In addition to capital, the length of thebusiness can also determine income because the length of the business is related to business experience and knowledgeabout consumer behavior. Technology can also affect the production of fish in Sibolga. The results of the data analysisshowed that capital, and technology had a simultaneous and significant effect on fish production in sibolga. Partially capitalvariables and technology partially affect fish production in Sibolga. In addition to capital, technology can also affect theproduction of fish in Sibolga. By using fish management technology can be more guaranteed quality. The more fishproduction that uses technology, the production marketed will be cheaper in price, the simpler the production technique thenthe price of production of fish marketed will be much more expensive and quality.